Subclinical Inflammatory Status in Rett Syndrome - Cortelazzo, Alessio; De Felice, Claudio; Guerranti, Roberto; Signorini, Cinzia; Leoncini, Silvia; Pecorelli, Alessandra; Zollo, Gloria; Landi, Claudia; Valacchi, Giuseppe; Ciccoli, Lucia; Bini, Luca; Hayek, Joussef (Mediators of Inflammation, 2014)
Inflammation has been advocated as a possible common central mechanism for developmental cognitive impairment. Rett syndrome (RTT) is a devastating neurodevelopmental disorder, mainly caused by de novo loss-of-function mutations in the gene encoding MeCP2. Here, we investigated plasma acute phase response (APR) in stage II (i.e., “pseudo-autistic”) RTT patients by routine haematology/clinical chemistry and proteomic 2-DE/MALDI-TOF analyses as a function of four major MECP2 gene mutation types (R306C, T158M, R168X, and large deletions). Elevated erythrocyte sedimentation rate values (median 33.0 mm/h versus 8.0 mm/h, P < 0.0001 ) were detectable in RTT, whereas C-reactive protein levels were unchanged ( P = 0.63 ). The 2-DE analysis identified significant changes for a total of 17 proteins, the majority of which were categorized as APR proteins, either positive ( n = 6 spots) or negative ( n = 9 spots), and to a lesser extent as proteins involved in the immune system ( n = 2 spots), with some proteins having overlapping functions on metabolism ( n = 7 spots). The number of protein changes was proportional to the severity of the mutation. Our findings reveal for the first time the presence of a subclinical chronic inflammatory status related to the “pseudo-autistic” phase of RTT, which is related to the severity carried by the MECP2 gene mutation.